Assessment of malalignment at the metacarpophalangeal joint of the rheumatoid hand using three-dimensional computed tomogram. Issue 1 (2nd January 2016) - Oh, Koei; Ishikawa, Hajime; Abe, Asami; Toyoshima, Yoichi; Inagaki, Katsunori; Murasawa, Akira
Abstract : Objective. For the assessment of rheumatoid hand, three-dimensional (3D) malalignment including flexed or rotational deformities and dislocation at the finger joint is one of the important findings. The objective of this study is to prove usefulness of 3D computed tomography (3DCT) for the accurate measurement of palmoulnar flexion deformity at the metacarpophalangeal (MP) joint of the rheumatoid hand. Methods. Swanson implant arthroplasty at the 2nd through the 5th MP joints was performed at 179 joints in 46 hands of 40 patients with rheumatoid arthritis. Pre-and postoperatively, evaluations included Larsen grade and ulnar flexion angle by an x-ray; and ulnar flexion angle, palmar flexion angle, and resected bone length by a 3DCT. Results. With progression of Larsen grade and the joint dislocation, ulnar flexion angle increased. Average ulnar flexion angle was 18.7 ± 16.0° (mean ± SD) in grade III, 38.4 ± 21.2° in grade IV, and 40.1 ± 21.1° in grade V, 29.6 ± 16.0°in "subluxation, " 24.8 ± 21.2° in "dislocation, " and 41.1 ± 22.2° in "severe dislocation." There was no significant difference between grade of the MP joint dislocation and palmar flexion angle. With progression of the MP joint dislocation, resected bone length increased. Conclusion. A 3DCT gives accurate information about deformity of the rheumatoid hand. Also, an appropriate length of bone resection can be determined in the preoperative planning.